Study Some Parameters of HCV Isolated From Sample of Hemophilic Patients in Children Welfare Teaching Hospitalin Medical City/Baghdad - alsabaq, yusra; alsaade, rayat; mohammed, eman (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s) : This study aimed at evaluating the seroprevalence of anti -HCV and studying thecorrelation between hemophilia and risk factors for acquiring HCV such as age , marital status &occupation among hemophilic patients .Methodology : 210 hemophilic patients in children welfare teaching hospital/medical city/Baghdad–Iraq(hemophilia center) were investigated using prepared questionnaire and tested for HCV infection, thosewere measuring patient’s age, hemophilia types and severity, marital status, residency and history ofprevious HCV infection .Results : Most hemophilic patients were hemophilia A at severe , hemophilia was at age group 20 – 29years , the majority of patients were unmarried and from urban areas , some of them had HCV infectionwhich was more among those had previous HCV infection .Recommendations : Health education level be increased among general population , all hemophilicpatients be commitment periodic HCV infection screening also blood and its products be strictly screened .